The Newly Sequenced Genome of Pisum sativum Is Replete with Potential G-Quadruplex-Forming Sequences-Implications for Evolution and Biological Regulation - Dobrovolná, Michaela; Bohálová, Natália; Peška, Vratislav; Wang, Jiawei; Luo, Yu; Bartas, Martin; Volná, Adriana; Mergny, Jean-Louis; Brázda, Václav (International journal of molecular sciences, 2022)
G-quadruplexes (G4s) have been long considered rare and physiologically unimportant in vitro curiosities, but recent methodological advances have proved their presence and functions in vivo. Moreover, in addition to their functional relevance in bacteria and animals, including humans, their importance has been recently demonstrated in evolutionarily distinct plant species. In this study, we analyzed the genome of Pisum sativum (garden pea, or the so-called green pea), a unique member of the Fabaceae family. Our results showed that this genome contained putative G4 sequences (PQSs). Interestingly, these PQSs were located nonrandomly in the nuclear genome. We also found PQSs in mitochondrial (mt) and chloroplast (cp) DNA, and we experimentally confirmed G4 formation for sequences found in these two organelles. The frequency of PQSs for nuclear DNA was 0.42 PQSs per thousand base pairs (kbp), in the same range as for cpDNA (0.53/kbp), but significantly lower than what was found for mitochondrial DNA (1.58/kbp). In the nuclear genome, PQSs were mainly associated with regulatory regions, including 5'UTRs, and upstream of the rRNA region. In contrast to genomic DNA, PQSs were located around RNA genes in cpDNA and mtDNA. Interestingly, PQSs were also associated with specific transposable elements such as TIR and LTR and around them, pointing to their role in their spreading in nuclear DNA. The nonrandom localization of PQSs uncovered their evolutionary and functional significance in the Pisum sativum genome.
Keywords: sekvence nukleotidů; Genome, Plant; genom rostlinný; transpozibilní elementy DNA; sequence prediction; G-Quadruplexes; 5' Untranslated Regions; 5' nepřekládaná oblast; Pisum sativum; Animals; DNA Transposable Elements; lidé; Humans; zvířata; G-quadruplex; hrách setý; G4 propensity; Base Sequence; G-kvadruplexy; chloroplast DNA